2012
DOI: 10.1002/emmm.201101045
|View full text |Cite
|
Sign up to set email alerts
|

A statin‐regulated microRNA represses human c‐Myc expression and function

Abstract: c-Myc dysregulation is one of the most common abnormalities found in human cancer. MicroRNAs (miRNAs) are functionally intertwined with the c-Myc network as multiple miRNAs are regulated by c-Myc, while others directly suppress c-Myc expression. In this work, we identified miR-33b as a primate-specific negative regulator of c-Myc. The human miR-33b gene is located at 17p11.2, a genomic locus frequently lost in medulloblastomas, of which a subset displays c-Myc overproduction. Through a small-scale screening wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 87 publications
3
84
0
1
Order By: Relevance
“…Consistent with this, several other genes were proposed to be responsible for the tumorigenic effect of 17p deletions (55). In agreement, a recent work has demonstrated that miR33b, a statin-regulated microRNA located at 17p11.2, targets MYC and regulating c-Myc-dependent medulloblastoma proliferation (35). In any case, additional studies will be required to define the precise contributions of miR-22 loss to neoplastic growth.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with this, several other genes were proposed to be responsible for the tumorigenic effect of 17p deletions (55). In agreement, a recent work has demonstrated that miR33b, a statin-regulated microRNA located at 17p11.2, targets MYC and regulating c-Myc-dependent medulloblastoma proliferation (35). In any case, additional studies will be required to define the precise contributions of miR-22 loss to neoplastic growth.…”
Section: Discussionsupporting
confidence: 66%
“…The miR-33b gene located at 17p11.2, a genomic locus frequently deleted in group 3 MB, was recently found to be up-regulated by lovastatin and, in turn, to repress MYC expression in two human cell lines (DAOY and D283) derived from MYC-driven primary MB patient samples (Takwi et al 2012). In DAOY cells, loss of miR-512.2 correlated with increased MYC expression (Lv et al 2012).…”
Section: Microrna Regulation Of Mycmentioning
confidence: 99%
“…This pathological upregulation is frequently due to chromosomal translocations leading to promoter rearrangement [4,5,6,7], gene amplification [7] and viral mediated insertional mutagenesis [8]. There is also evidence that c-MYC expression is suppressed by miRNAs [9,10]. …”
Section: Introductionmentioning
confidence: 99%